Validation of the COURAGE Built Environment Self‐Reported Questionnaire. (16th July 2013) - Raggi, Alberto; Quintas, Rui; Bucciarelli, Paola; Franco, Maria Grazia; Andreotti, Alessandra; Miret, Marta; Zawisza, Katarzyna; Olaya, Beatriz; Chatterji, Somnath; Sainio, Päivi; Frisoni, Giovanni Battista; Martinuzzi, Andrea; et al.
<x xml:space="preserve">Abstract</x> The built environment (BE) impacts on people's disability and health, in terms of overweight, depression, alcohol abuse, poor self‐rated health and presence of psychological symptoms; it is reasonable to assume that BE also impacts on participation levels. This paper presents the validation of the COURAGE Built Environment Self‐Reported Questionnaire (CBE‐SR), an instrument designed to evaluate BE in the context of health and disability. Subjects participating to COURAGE, a cross‐sectional study conducted on 10 800 citizens of Poland, Finland and Spain, completed a protocol inclusive of the CBE‐SR. Psychometric properties and factor structure were analysed, and factor scores created. Gender differences, differences between persons from different age groups and persons reporting the environment as facilitating, hindering or neutral were calculated. Eight items were deleted so that the final version of CBE‐SR comprises 19 items. Cronbach's alpha ranged from 0.743 to 0.906, and test–retest stability was demonstrated for the majority of items. Four subscales were identified: Usability of the neighbourhood environment; Hindrance of walkable environment; Easiness of use of public buildings, places and facilities; and Risk of accidents and usability of the living place. Younger respondents reported their neighbourhood as more usable but perceived walkways as more hindering and public buildings as less easy to use; gender differences were almost inexistent. The CBE‐SR is a four‐scale instrument with good psychometric properties that measures the person–environment interaction. It is sensitive across age groups and is consistent with the subject's overall judgement of the degree to which the environment is facilitating or hindering. Copyright © 2013 John Wiley & Sons, Ltd. Key Practitioner Message Poor built environments have a negative impact on the level of a person's participation. However, instruments measuring the person–environment interaction are lacking. The CBE‐SR is a valid and reliable instrument that researchers can use to assess the relationships between the intrinsic health state and the objective features of the environment. Understanding this relationship would provide further insight into the need of addressing the individual's functioning either by means of interventions directed to the individual or by making changes to the individual's environment.